Maltrato infantil y su incidencia en el comportamiento social de los estudiantes de la Unidad Educativa Juan E. Verdesoto del cantón Babahoyo, provincia de los Ríos año 2017. - Saldivia Delgado, Jefferson Joel (2018)
The social environment is the complement in the formation of the students, it depends on that so that they obtain an adequate and positive formation, it is necessary to organize in a better way the environments in which the students develop to contribute with their education and that this is not reason for inappropriate behavior that marks the lives of children, is that in many cases students with abuse are seen either at home, between friends or at the school and they respond with aggressive, timid or inappropriate behavior. In the present research work is intended to show the influence of child abuse in the social behavior of the students of the Educational Unit Juan E. Verdesoto Babahoyo canton, province of Los Ríos year 2017, for which it is necessary to determine the methodology, starting by the type of exploratory, descriptive and explanatory research applied in a systematic way according to the needs, the inductive and deductive methods, the techniques of information collection beginning with the observation, then with interview and surveys, whose instrument was the questionnaire of semi structured questions, open and closed, formally and informally. It should be noted that as a result of the present work it is concluded that there are students with child abuse and that generally they influence their behavior negatively, react in various ways and act defensively against their peers who sometimes only want to share games with them For this reason, the proposal for the elaboration of a school workshop program for parents is presented aimed at raising awareness about the consequences of child maltreatment in the students of the Juan E. Verdesoto Educational Unit of the Babahoyo county, province of Los Ríos.